The development of method for increasing the decision making efficiency in organizational and technical systems - Lytvynenko, Oleksandr; Bieliakov, Robert; Vakulenko, Yuliia; Hrinkov, Volodymyr; Pokhodenko, Borys; Boiko, Sergey; Kanishov, Viacheslav; Drozdyk, Yevhenii; Kovtun, Yevhenii; Leinyk, Dmitry (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is decision making processes in decision making support systems. The subject of the research is a method of decision making in management tasks using the walrus flock algorithm (WA), an advanced genetic algorithm and evolving artificial neural networks. A method of finding solutions using an improved walrus flock algorithm is proposed. The research is based on the walrus flock algorithm for finding a solution to the object’s condition. Evolving artificial neural networks are used to train walrus agents and an advanced genetic algorithm is used to select the best walrus agents. The method has the following sequence of actions: – input of initial data; – WA numbering in the flock; – determination of the initial speed of WA; – display of WA along the search plane; – preliminary assessment of the WA search area; – classification of food sources for WA; – sorting of the best WA individuals; – an update of WA positions; – WA migration; – checking the presence of a predator; – checking the stop criterion; – escape and struggle with predators; – checking the stop criterion; – training of WA knowledge bases; – determination of the amount of necessary computing resources, intelligent decision making support system. The originality of the proposed method lies in the placement of WA taking into account the uncertainty of the initial data, improved procedures of global and local edge taking into account the degree of noise of data on the state of organizational and technical systems. The use of the method makes it possible to increase the efficiency of data processing at the level 13–16 % due to the use of additional improved procedures. The proposed method should be used to solve problems of evaluating complex and dynamic processes